Can education for democratic citizenship be a task for company-based training? - Hackel, Monika [Verfasser] (My University, 2024)
"According to the Vocational Training Act, a holistic educational remit forms a core element of training in the dual system. In light of increasing political disenchantment and popularism, more and more companies providing training are wondering which aspects of civic education they can impart without running the risk of being perceived by the trainees as ideologically biased or manipulative. This article illustrates the points of reference offered in this regard by the standards in all occupational profile positions, which have been applicable since 2021. One of the aims is to foster cross-cutting competencies, which also form part of the employability skills set in the modern world of work, over the entire apprenticeship. These also include societal and democratic competencies and values such as participation, the ability to enter into discourse, solidarity and tolerance." (BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; 370; Betriebliche Berufsausbildung; Berufsbildposition; Handlungskompetenz; Demokratie